Transforming emergent Icelandic tourist sites into sustainable and responsibly managed destinations: A case study of the 2021 Geldingadalur eruption in Iceland - Stephanie Elizabeth May Langridge 1991- (2021)
There is a gap in policy making surrounding sustainable and responsible management of emergent natural tourist sites in Iceland. The 2021 volcanic eruption in Geldingadalur is examined in a case study to establish an environmental, social and economic context, and examine an active collaboration between stakeholders to develop a natural site from its conception. Perceived issues from a stakeholder perspective highlight key challenges, among them funding, staffing, access and transparency over decisions that affect the perception of the site’s development. Sixteen respondents were interviewed from five stakeholder groups: municipal actors and representatives, landowners, civil protection, companies and operators, and representatives from the Ministries of Tourism, and Environment and Natural Resources on behalf of the government. A constant comparative method was used to analyse qualitative data across stakeholder segments. Five core themes of authority, responsibility, safety, funding and access were incorporated into a core category, responsible management. Perceived environmental, social and economic sustainability challenges are situated within three responsible tourism behaviours: identifying issues that need a response, stakeholders assuming authority for issues and the empowerment of stakeholders and their capacity to act. Results show that stakeholders who assume authority over issues are more likely to succeed if other stakeholders empower and support them. Stakeholders call for more transparency, accountability and enforceability for responsible management approaches, particularly funding. All stakeholders agree that responsible management of a site involves restricting access in some way to avoid overconsumption of resources and infrastructure. Communication and agreement between stakeholders regarding definitions and applications of sustainable and responsible behaviours are essential for the success of management efforts and policies relating to the development and administration of natural sites.